CHALLENGES OF IMPLEMENTING THE GRAMMAR TRANSLATION METHOD IN DIVERSE EFL CONTEXTS (Лучшие интеллектуальные исследования, 2025)
Abstract: The Grammar Translation Method (GTM) has been a longstanding approach in teaching English as a Foreign Language (EFL). However, its implementation in diverse EFL contexts presents unique challenges. This article explores the methodological aspects that hinder the effective application of GTM in multicultural classrooms. Through a review of existing literature and qualitative analysis, this study identifies key challenges including linguistic diversity, varying proficiency levels, cultural differences, and limited engagement. The findings suggest that while GTM can be beneficial for grammar acquisition, its effectiveness is often compromised in heterogeneous environments. Recommendations for adapting GTM to meet diverse learner needs are discussed.